Conservative Management of a Congenital Seminal Vesicle Cyst Associated with Ipsilateral Renal Agenesis Revealed by Cystitis: One Case Report - Youness Ahallal; Mohammed Fadl Tazi; Abdelhak Khallouk; Jalaleddine Elammari; Mohammed Jamal Elfassi; Moulay Hassan Farih (Case Reports in Urology)
Seminal vesicle cyst is an extremely rare disease. Its association with ipsilateral renal agenesis is even more exceptional. We present herein one case of a 16-year-old male who presented with a four-month history of lower urinary tract symptoms (LUTSs) and micturition pain. The digital rectal examination revealed a small mass arising from the prostate. The urine culture showed that E. coli is sensitive to all antibiotics tested. Transrectal ultrasound (TRUS) revealed a cystic mass in the outer prostate. Seminal vesicle cyst and left renal agenesis were confirmed by magnetic resonance imaging (MRI). Maximum flow (Qmax) at uroflow was greater than 15 mL/sec. We therefore decided to manage this disease conservatively with alpha blockers and antibiotics. After 6-month' followup the patient did not report any complain and the uroflow test was similar to a normal urination. From one case report and literature review, the authors suggest a diagnostic and therapeutic strategy for the management of this rare condition.